1989
DOI: 10.1002/rcm.1290030508
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐spray mass spectrometry of marine neurotoxins

Abstract: Ion-spray mass spectrometry was investigated for the analysis of three marine neurotoxins: domoic acid, saxitoxin and tetrodotoxin. All three compounds gave positive-ion spectra with abundant ions of protonated molecules and no significant fragmentation. Domoic acid gave a negative-ion spectrum with a strong [M-H]- ion. Tandem mass spectrometry provided useful fragment-ion spectra for all compounds. Detection limits for flow injection analyses with selected-ion monitoring were determined to be 30 pg for saxito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
1

Year Published

1994
1994
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(40 citation statements)
references
References 21 publications
3
36
0
1
Order By: Relevance
“…Several laboratories have reported improvements to the method, such as the in situ method for preparation of the reagent (Yoshida et al, 1988;Quilliam et al, 1998) and better cleanup procedures (Quilliam, 1995;Stabell et al, 1991). LC combined with mass spectrometry (LC/ MS) is another method that is gaining acceptance as a good quantitative and confirmatory method for toxins (Quilliam, 1995;Quilliam et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratories have reported improvements to the method, such as the in situ method for preparation of the reagent (Yoshida et al, 1988;Quilliam et al, 1998) and better cleanup procedures (Quilliam, 1995;Stabell et al, 1991). LC combined with mass spectrometry (LC/ MS) is another method that is gaining acceptance as a good quantitative and confirmatory method for toxins (Quilliam, 1995;Quilliam et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…15 This acid is volatile and is compatible with HPLC/MS. It has been shown that a low concentration of a volatile buffer at low pH maximizes ionization efficiency and sensitivity for ISP-MS. 16 Our current study applies HPLC with ionspray ionization and a tandem mass spectrometry strategy (HPLC/ISP-MS/MS) to the detection of paraquat and diquat in water samples. Multiple reaction monitoring (MRM) was chosen because of the added selectivity that it provides.…”
mentioning
confidence: 99%
“…Recently, the U.S. Food and Drug Administration increased the permissible level of DA in Dungeness et al, Grimmelt et a]., 19901, direct detection-UV HPLC [Lawrenceet al, 1989a[Lawrenceet al, , 1991Quilliametal., 1989a1, chemical and fluorescence derivative HPLC [Lawrence et a]., 1989b; Pockington et al, 19901, LC or GC-MS [Quilliam et al, 1989b;Pleasance et a]., 1990; Musser et al, 19921, radio immunoassay (RIA), and enzyme-linked immunosorbant assay (ELISA) [Newsome et al, 19911. Of these methods, HPLC with direct detection of DA at 242 nm (A max) combined with a solid phase extraction (SPE) clean-up procedure has evolved as the method of choice for rapid monitoring purposes.…”
Section: Introductionmentioning
confidence: 99%